Influence Of Corporate Social Responsibility(CSR) In Building Corporate Reputation Through Employee Trust As Mediating Variable - Farid Nur Aidy; Yoppi Priatmoko; Andiany Indra P (Jurnal Ilmiah Manajemen dan Bisnis, 2021)
This study aims to examine the effect of Corporate Social Responsibility (CSR) through Employee Trust on the reputation of the company PT Wijaya Karya (Persero) Tbk. To overcome this, data was collected through questions that were disseminated online using a google form. Responses from 150 respondents with a sample of employees of PT Wijaya Karya (Persero) Tbk, then analyzed using PLS-SEM through SmartPLS3 Software. The data collected was tested using the Validity Test and Reliability Test. To find out the results of the analysis of the inner model, outer model. As for testing the hypothesis using the bootstrap method. The results of this study indicate that there is a positive influence of CSR activities and perceptions of CSR programs on the Company's Reputation. the perception of CSR activities and CSR activities will increase employee confidence to improve the company's reputation.